(3GdSdSHjd GdeYjf aj GdWQGFb GdCQHYjfs - (3GdSfhSj , eMeO Hf Ydj Hf GdSfhSj, CHh YHO Gddg,J (B1276 (3g` s
(3ChdgG (B:s
(3hHYO abO MUd dfG hddg GdMeO GdJFGe HCFeI CYdGe hLgG HPI ef Cgd Gddg aNGe hhUd EdjfG ef WQGFbge s
(3BNQgG (B:s
(3aEPG NJeJ HgG aCeQi gjf hLejY eG eaJbQ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B14s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(1521 (3O(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs